Review on Advancement in Cosmetic Science For Melasma - Adalinge, Shravani Arvind; Adalinge, Dr. Shruti.A.; Naikawadi, Nishigandha. D.; Redasani, Dr. V.K. (Asian Journal of Pharmaceutical Research and Development, 2024)
Melasma, a common hyperpigmentation disorder, poses a significant challenge in the field of dermatology and cosmetic science. Characterized by symmetrical, brownish facial pigmentation, melasma primarily affects women of reproductive age, with a notable impact on quality of life. Despite its prevalence, effective and long-lasting treatments remain elusive. This review explores the latest developments in cosmetic science aimed at addressing melasma, focusing on innovative formulations, ingredients, and technologies.Traditional and contemporary cosmetic approaches to melasma, including the use of topical agents such as hydroquinone, retinoids, and corticosteroids. Additionally, the review discusses emerging ingredients like tranexamic acid, niacinamide, kojic acid, and botanical extracts known for their skin-lightening properties. The review concludes by emphasizing the need for a multifaceted approach in cosmetic science to effectively manage melasma. By combining traditional and novel ingredients, optimizing delivery systems, and integrating advanced technologies, cosmetic formulations can offer improved efficacy and patient satisfaction in the management of melasma. Future directions for research and development are also discussed, with an emphasis on personalized skincare regimens tailored to individual patient characteristics.